The Effect of Quality Care on Patient Loyalty Mediated with Patient Satisfaction and Moderated by Age and Gender (Study in Outpatients at a Private Hospital) - Ricca Ricca; Ferdi Antonio (International Journal of Applied Business and International Management, 2021)
An increasingly competitive business climate and changes in patient behavior, fostering hospital managers to pay more attention in regard to factors that could affect patient loyalty. Quality care is well known as a major contributor to patient loyalty. The purpose of this study is to examine the effect of quality care on patient loyalty with patient satisfaction as the mediating variable, while age and gender as the moderators. This research model was tested empirically in outpatients at a private hospital. The results demonstrate that quality care has a significant positive effect on patient loyalty. Several managerial implications were found for hospital management to increase patient loyalty, especially considering the gender of the patient in providing services.